2004
DOI: 10.1590/s1678-77572004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Biological compatibility of some types of endodontic calcium hydroxide and glass ionomer cements

Abstract: BIOLOGICAL COMPATIBILITY OF SOME TYPES OF ENDODONTIC CALCIUM HYDROXIDE AND GLASS IONOMER CEMENTS BIOCOMPATIBILIDADE DE ALGUNS TIPOS DE CIMENTO ENDODÔNTICO À BASE DE HIDRÓXIDO DE CÁLCIO E CIMENTOS DE IONÔMERO DE VIDROhe purpose of this work was to evaluate the biological compatibility of the Sealapex, Apexit, Sealer 26 and Ketac Endo endodontic cements. Polyethylene tubes containing these cements were implanted in the subcutaneous tissue of 40 (forty) rats. The animals were sacrificed after 14 and 90 days. A de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…There was no evidence of calcification or necrosis. These findings were in accordance with Valera et al (2004), Yaltirik et al (2004) and de Morais et al (2006). This mild reaction may be due surgical trauma during the implantation of tube.…”
Section: Discussionsupporting
confidence: 88%
“…There was no evidence of calcification or necrosis. These findings were in accordance with Valera et al (2004), Yaltirik et al (2004) and de Morais et al (2006). This mild reaction may be due surgical trauma during the implantation of tube.…”
Section: Discussionsupporting
confidence: 88%
“…The implementation methodology of polyethylene tubes in the connective tissue of mice used in this study was based on Torneck (1966) experiments, which demonstrated the acceptability of this material by the subcutaneous connective tissue of animals, as well as, since it is a controlled method with few variables and low cost (Garcia et al, 2008;Valera et al, 2004). Besides, polyethylene tubes mimic the conditions of the root canal, since only the final portion of the tube, corresponding to the root apex, the test material will contact the tissue and the opposite side sealed with biocompatible material will serve as control (Zmener et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on tissue reactions to implanted test specimens into soft and bone tissues in experimental animals (rats, guinea pigs) have documented a differential response to various endodontic materials . ZnO–eugenol‐ and resin‐based materials typically cause a pronounced initial inflammatory reaction, which diminishes with time especially for the epoxy‐based products .…”
Section: Animal Experimentsmentioning
confidence: 99%